Social Entrepreneurship as an Instrument to Empowering Small and Medium Enterprises: An Islamic Perspective - Abdullah, Moha Asri; Hoetoro, Arif (Danishgah-i Azad-i Islami, 2011)
Small and Medium Enterprises (SMEs) are reckoned as the main player in domestic economic activities. This paper tries to contribute to the development and understanding of SMEs by encompassing social entrepreneurship as an empowering instrument. Considering the latest thought for intellectual milieu, this paper discloses the buried interlocking principles for social entrepreneurship by Islamic doctrine. The plot of current research is generated by few related frameworks that are in line with the Islamic notion which reviews the roles and obstacles of SMEs development. Given the extensive attentions on Islamic values, this paper reveals that every Muslim entrepreneur and related supporting agent must change their old vision into the new one- that they should work more productively. Besides, in many countries, several programs to empower SMEs have practically exposed its significant need and development. Therefore, a number of policies, initiatives and objectives are drawn to build social entrepreneurship to empower SMEs. However, empowering SMEs can change Muslim entrepreneurs’ vision regarding fair production which is attributed by Islam. Therefore, there is a need to a condition in which the cooperation between Islamic financial institutions and SMEs is naturally embedded in social capital structure.